Fulfillment of Child Support Rights After Divorce by a Convicted Father - Anggraeni, Dinda Restya; Sulastri, Sulastri (Jurnal Daulat Hukum, 2025)
Children are a mandate and gift from God who naturally have dignity and honor as human beings. On that basis, children have the right to receive full protection, especially regarding the protection of their basic rights. According to Government Regulation (PP) Article 1 No. 59 of 2019, "children's rights are part of human rights that must be guaranteed, protected, and fulfilled by parents, families, communities, the state, the government, and local governments." Child care includes their rights, such as to sustenance, health, clothing, education, and housing, as well as the right to receive love, attention, and protection from parents. This study uses a normative legal method through a statutory approach. The data in this study were collected through library research data collection techniques. In conclusion, the fulfillment of children's rights to sustenance after divorce is a legal obligation that remains attached to parents, especially fathers, even though the marriage bond has ended. Children still have the right to proper care and education until adulthood or are able to stand alone, as regulated in various laws and regulations, such as the Marriage Law, the Compilation of Islamic Law, and special regulations that apply to certain professions such as civil servants, police, and military. Negligence in fulfilling children's needs can be categorized as a form of neglect that has implications for criminal and civil sanctions.